A Review and Analysis of the Musical Connotation of Tchaikovsky's Symphony No. 6 in B Minor "Pathétique" - Liu , Junxiang (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
Music, hailed as the first of all the art forms, has always been known to exist in a wide range of human aesthetic spheres across borders, nationalities, regions, and ideological mediums. Pyotr Ilyich Tchaikovsky was a great composer famous for combining the best of Russian folk music and Western European classical music. Tchaikovsky devoted his life to music composition and composed many musical works in different genres, such as symphonies, operas, stage music (dances), concertos, concert overtures, chamber music, and vocal romances. Employing an "ontological analysis study," this paper tries to analyze the musical connotation of Pyotr Ilyich Tchaikovsky's last masterpiece in his life, Symphony No. 6 in B minor "Pathétique." It focuses on his personality, artistic experience, and compositional characteristics to comprehensively organize and summarize the great work's composition features and aesthetic values. This masterpiece is the epitome of the composer's lifelong journey, his lament for the desolation of life, and also the closing summary of his life's beauty and broken dreams. It shocks people's hearts with its tragic "Pathétique" beauty.